'Clickable' cyclopentadienyl iron carbonyl complexes for bioorthogonal conjugation of mid‐infrared labels to a model protein and PAMAM dendrimer. (11th February 2019) - Fischer‐Durand, Nathalie; Lizinska, Daria; Guérineau, Vincent; Rudolf, Bogna; Salmain, Michèle
Abstract : Owing to the intrinsic limitations of the conventional bioconjugation methods involving native nucleophilic functions of proteins, we sought to develop alternative approaches to introduce metallocarbonyl infrared labels onto proteins on the basis of the [3 + 2] dipolar azide‐alkyne cycloaddition (AAC). To this end, two cyclopentadienyl iron dicarbonyl (Fp) complexes carrying a terminal or a strained alkyne handle were synthesized. Their reactivity was examined towards a model protein and poly (amidoamine) (PAMAM) dendrimer, both carrying azido groups. While the copper (I)‐catalysed azide‐alkyne cycloaddition (CuAAC) proceeded smoothly with the terminal alkyne metallocarbonyl derivative, labelling by strain‐promoted azide‐alkyne cycloaddition (SPAAC) was less successful in terms of final coupling ratios. Infrared spectral characterization of the bioconjugates showed the presence of two bands in the 2000 cm −1 region, owing to the stretching vibration modes of the carbonyl ligands of the Fp entities. Abstract : Azide ‐ alkyne cycloadditions between BSA or PAMAM dendrimer carrying azide groups and cyclopentadienyl iron dicarbonyl (Fp) complexes carrying a terminal or a strained alkyne handle were examined. While the CuAAC proceeded smoothly, the SPAAC was less successful. Infrared spectra of the bioconjugates displayed two bands in the 2000 cm‐1 region, owing to the stretching vibration modes of the carbonyl ligands of the Fp entities.